Colonisation and infection with antibiotic-resistant organisms in patients in the adult intensive care unit, hospital for tropical diseases, Ho Chi Minh City, Vietnam - Thuy, D (2018)
In Vietnam, data about colonisation and subsequent infections with antibiotic-resistant organisms (AROs) are limited, particularly from intensive care units (ICUs). A prospective longitudinal study was conducted in Adult ICU, Hospital for Tropical Diseases, Vietnam from 10th November 2014 to 14th January 2016 to characterize colonisation, identify risk factors for colonisation and understand its relationship with infections by Staphylococcus aureus, Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa, and Acinetobacter spp.. 63.1% (529/838) of patients admitted to ICU were colonised with AROs. 61.3% (223/364) of patients with an ICU stay >48 hours acquired AROs colonisation in ICU. Increased Charlson Comorbidity Index score and receipt of antimicrobial therapy on ICU admission were significant risk factors for AROs acquisition. The proportion of patients with hospital-acquired infections (HAIs) was 23.4% (85/364), and AROs accounted for 41.5% (44/106) of pathogens causing HAIs. Vascular catheterization was identified as a risk factor for ICU-acquired bloodstream infection. Of 67 Staphylococcus aureus isolates identified by conventional microbiology, 6 isolates (9%) were sequenced as Staphylococcus argenteus. Multilocus sequence typing (MLST) analysis indicated matching sequence types of infecting and previously colonizing isolates in 90% (9/10) and 94.4% (17/18) patients with HAIs by Staphylococcus aureus and Klebsiella pneumoniae, respectively. Phylogenetic analysis confirmed that ICU patients became infected with their previously colonizing Staphylococcus aureus ST188 (4 patients) or Klebsiella pneumoniae ST17, ST23 and ST86 (6 patients). Whole-genome sequencing helped to disprove 3 patient-to-patient transmission events (1 Staphylococcus aureus and 2 Klebsiella pneumoniae) that were suggested by MLST, and identified one additional Staphylococcus aureus transmission which was missed by other methods. This thesis provides evidence of the high burden of antimicrobial resistance in Vietnam along with high rate of colonisation and infections with AROs. Therefore, the implementation of infection control measures and antimicrobial stewardship programs is urgently needed in Vietnam.